FRAY JOSÉ ANTONIO LIENDO Y GOICOECHEA Y EL DESARROLLO DE LAS CIENCIAS FÍSICAS EN CENTRO AMÉRICA - Solano , Francisco Enríquez (2005)
This article deals with the formal institutionalization process and the foundation of educational institutions in Mexico and Central America, particularly as refers to the Guatemalan case, represented by Fray José Antonio de Liendo y Goicoechea and his influence on the development of physical science in the Isthmus.